Assistance of Sharia Banking Finance Program in MSME Development in Malang Regency - Mohammad Rizal; Muhammad Ridwan Basalamah (Journal of Interdisciplinary Socio-Economic and Community Study, 2021)
The MSME sector has a vital role in supporting the economy of Malang Regency. The factor that makes it difficult for MSMEs to access Islamic banking financing is an unorganized financial administration system characterized by operational costs inseparable from household expenses. Technical constraints make MSME owners less concerned about their long-term business goals or strategic plans. Karangsuko Village, located in the Malang Regency area, most of the population still relies on the MSME sector as a livelihood. This service aims to make MSME actors understand financial management, sharia accounts, financing rules from Islamic banks, preparation of financial reports, and the formation of proposals for submitting financing to Islamic banks.